The Households of the Princesses: Service and Representation through the first Household of Infanta Leonor of Aragon (1366-1375) - Diana Pelaz Flores (Royal Studies Journal, 2023)
The court service of queens and infantas demonstrates the complexity and changing nature of its composition over time. These are not only changes brought about by the needs of the service itself, but also by political issues, family alliances, and questions of representation. The courtly customs of each kingdom generate a particular identity, while at the same time offering protection to their caregivers and safeguarding the interests of their kingdom of origin. This paper looks at the particular case of the entourage that accompanied Leonor of Aragon on her first trip to Castile (1366), to celebrate the entry into the kingdom of Enrique of Trastamara, and his subsequent coronation. This episode was selected because it combines the incorporation of the Infanta into the entourage of her future mother-in-law, Juana Manuel de Villena, long before her marriage, and also because it reveals the strength of the political and military interests of her father, King Pedro IV of Aragon. As the Infanta was an eight-year-old maid, the role of her officers and servants is key, due to the tasks they performed and the decisions they took to protect the Infanta and the image of the Crown of Aragon.